2014
DOI: 10.1016/j.marenvres.2013.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the diatom-derived polyunsaturated aldehyde 2-trans,4-trans decadienal on the feeding, survivorship and reproductive success of the calanoid copepod Temora stylifera

Abstract: Many diatoms, a major class of unicellular algae contributing to over 45% of oceanic primary production, are known to induce deleterious effects on reproductive processes in crustacean copepods. This is mainly due to the production of teratogenic oxylipins, including polyunsaturated aldehydes (PUAs). Here we tested the direct effect of the PUA 2E,4E-decadienal (DD) on feeding activity, survivorship and reproductive success of the calanoid copepod Temora stylifera. DD-inoculated cultures induced high mortality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…These results are also in agreement with a recent study by Kâ et al (2014) who reported high mortality above 3.0 mg mL À1 decadienal in the copepod Temora stylifera. Furthermore, these authors noted that males were more sensitive than females to high concentrations of decadienal whereas the present results show the opposite trend.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…These results are also in agreement with a recent study by Kâ et al (2014) who reported high mortality above 3.0 mg mL À1 decadienal in the copepod Temora stylifera. Furthermore, these authors noted that males were more sensitive than females to high concentrations of decadienal whereas the present results show the opposite trend.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have reported that exposure of embryos and larvae to PUA can severely impact development, growth and fitness of other copepod species (Miralto et al, 1999;Caldwell et al, 2002;Carotenuto et al, 2002;Ianora et al, 2004Ianora et al, , 2011Vargas et al, 2006;Poulet et al, 2007;Kâ et al, 2014). Decadienal has also been shown to potentially impact other marine organisms (Romano et al, , 2010Caldwell et al, 2005;Tosti et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations